Simulator of Hydroacoustic Signals for a Complex System of Underwater Environment - Klionskiy, D. M.; Kaplun, D. I.; Geppener, V. V.; Voznesenskiy, A. S. (Progress in Electromagnetics Research Symposium, 2019)
The paper is devoted to simulating and processing different types of hydroacoustic signals. The analysis of these signals helps us to detect marine objects and design complex systems of underwater environment. We introduce a fast technique of hydroacoustic signal processing in the frequency domain based on adaptive spectral analysis and wavelet smoothing. This technique is applicable for studying local features of hydroacoustic signals in the frequency domain and classifying them based on spectral characteristics.